The transport of water in a cellulose foam. (November 2022) - Das, Ratul; Deshpande, Vikram S.; Fleck, Norman A.
Abstract: A novel experimental protocol and analysis technique is developed to determine whether water rise in a cellulose foam is by capillary flow alone, or is by capillary flow followed by diffusion. The literature is divided in the interpretation of the water rise versus time characteristic in the foam, and our study suggests that capillary flow dominates. The present study reveals that the foam can be idealised as a spectrum of individual capillary tubes; the probability density function of tube radius is obtained from a systematic set of siphon discharge experiments on inverted U-tubes made from the foam. We show that the capillary tube radii range from 0 . 1 μ m to 100 μ m, with two distinct peaks in probability density at 0 . 5 μ m and 10 μ m . The nature of the flow within the U-tube is confirmed by interrupting a siphon experiment and measuring the density profile along the length of the inverted U-tube by in-situ X-ray computed tomography. The probability density function is then used to predict the transient rise of water in a vertical column of dry foam. Graphical abstract: Highlights: Critical experiment shows an established capillary flow above the inferred Jurin height for cellulose foam. Dry cellulose foam is idealised as a bundle of individual capillary tubes of varying radius. A novel experimental technique is developed in order to estimate the probability density distribution of capillary tube radius.